Answer :

We have 36° + 9° = 45°


tan(36° + 9°) = tan 45°


We know that



tan 36° + tan 9° = 1 – tan 36° tan 9°


tan 36° + tan 9° + tan 36° tan 9° = 1


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses